ANALISA FISIKOKIMIA PATI PADA 5 JENIS PISANG - Riyanto Riyanto; Dosna A. Pasaribu (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2021)
The objectives of this research was (i) to compare physicochemical starch (amilum) such as pH, water content, ash and sugar (Glucose) concentration of 5 varieties of bananas ( Pisang Kepok, Pisang Ambon, Pisang Barangan, Pisang Nangka dan Pisang Mas). Those are commonly consumed in Indonesia, (ii) to analyze the correlation among the parameters. After the starch was extracted and analyzed, the results were as fallows: based on analysis of variance, pH varies among the bananas. LSD (least significant defernces) test, LSD 0.05 = 0.43 concluded that pH of starch pisang ambon and pisang barangan were higher than pH pisang kapok, pisang nangka and pisang mas. The highest water content was at starch of pisang kapok, 4.64%, whilist the lowest water content at starch of pisang mas, only 0.96%. The highest ash content was starch of pisang ambon, 2.60 %, whilist the lowest was at pisang mas, only 1.42%. The highest sugar content was at starch of pisang kapok and pisang ambon, both have 22.19 and 19.02 mg/ ml, whilist the lowest sugar content was at pisang barangan that only have 16.08 mg/ 100 ml. Correlation among the parameters shows that thare was no correlation between pH with water, ash and sugar content. The highest correlation accured between water content and sugar content, in which r = – 0.89 that means the more water content will be the less sugar content and vice versa. The second highest correlation accured between ash content with water content in which r = 0.76 that means the more water content will be the more ash content. The correlation between ash content and sugar content was relatively low, r = - 0.44